Effectiveness of Nurse Led Intervention on Health Related Quality of Life among Children with Sickle Cell Disease in Oman: A Pilot Study - Pandarakutty, Suthan (Adv Hematol, 2019)
Introduction. The children with Sickle Cell Disease (SCD) generally have poor Health Related Quality of Life (HRQOL). The study aimed to evaluate the effectiveness of nurse led intervention on HRQOL among children with SCD. METHODS: A total of 30 samples were selected using convenient sampling. Children with SCD and their caregivers completed Pediatric Quality of Life Inventory (PedsQL) SCD-Module version 3.0. The nurse led intervention was given to the study group for 10 consecutive weeks. The control group received the routine medical care. On completion of 10 weeks, the post-test was conducted. RESULTS: The participants in study group had poor HRQOL scores (P > 0.05) in pre-test. After nurse led intervention, the HRQOL score in the study group significantly improved (P > 0.05) in pre-test. After nurse led intervention, the HRQOL score in the study group significantly improved (Discussion. Therefore nurse led intervention is effective in improving HRQOL among children with SCD.